Metal mixing in the r-process enhanced ultrafaint dwarf galaxy reticulum II - Ji, Alexander; Simon, Joshua D.; Roederer, Ian U.; Magg, Ekaterina; Frebel, Anna; Johnson, Christian I.; Klessen, Ralf S.; Magg, Mattis; Cescutti, Gabriele; Mateo, Mario; Bergemann, Maria; Bailey, John I. (The astronomical journal, 2023)
The ultrafaint dwarf galaxy Reticulum II was enriched by a single rare and prolific r-process event. The r-process content of Reticulum II thus provides a unique opportunity to study metal mixing in a relic first galaxy. Using multi-object high-resolution spectroscopy with VLT/GIRAFFE and Magellan/M2FS, we identify 32 clear spectroscopic member stars and measure abundances of Mg, Ca, Fe, and Ba where possible. We find of the stars are r-process-enhanced, with a mean and unresolved intrinsic dispersion σ [Ba/H]<0.20. The homogeneous r-process abundances imply that Ret II’s metals are well mixed by the time the r-enhanced stars form, which simulations have shown requires at least 100 Myr of metal mixing in between bursts of star formation to homogenize. This is the first direct evidence of bursty star formation in an ultrafaint dwarf galaxy. The homogeneous dilution prefers a prompt and high-yield r-process site, such as collapsar disk winds or prompt neutron star mergers. We also find evidence from [Ba/H] and [Mg/Ca] that the r-enhanced stars in Ret II formed in the absence of substantial pristine gas accretion, perhaps indicating that ≈70% of Ret II stars formed after reionization.
Gesehen am 05.04.2023